Business Model Development Strategy for Frozen Food Micro-Businesses in The New Normal Era (Case Study: CV XYZ) - Ardelia Nadhilah Rosyad; Rizal Syarief; M. Faiz Syuaib (Indonesian Journal of Business and Entrepreneurship (IJBE), 2022)
The limitation of community movement in the new normal era has changed consumer behaviour to frozen food products, and digital marketing has been used to carry out a transaction. CV XYZ, a company that produces frozen food, must optimize the existing opportunities and utilize its strengths. The high level of social hygiene and the increasing demand for food integrity has become a challenge the company is facing today. Other than that, the company is now facing several obstacles on product development and channel limitation. Therefore, this research is aimed to identify the business model available, develop an alternative business strategy and create a new business model innovation. The data sources are from primary and secondary data; the primary data are observation, interview, FGD with the research experts, businessmen, and consumer survey. The secondary data used are literature studies such as journals, thesis, dissertation, economic data, and textbooks. Data processing techniques are carried out by analyzing business model canvas, SWOT, internal factor evaluation, and external factor evaluation , grand strategy, and 360° business model innovation. The result of SWOT analysis maps the company in quadrant one, which indicates the company is in high market growth and strong competitive position, so the company needs to improve its business model through BMI 360° analysis model. This model is used to help see the business activity process from creating value in the upstream until it can become the core competition downstream of a business process. Keywords: 360° business model innovation, business model canvas, small and medium enterprise (SMEs), SWOT, value